Emergence of Feline Sporotrichosis near Brazil Border, Argentina, 2023–2024 - Katherina Alicia Vizcaychipi; María Cecilia López-Joffre; Mónica Martínez; Jerson Andrés Cuéllar-Sáenz; Marina Ramos; Celeste Agüero; Natalia Olsina; Emanuel Grassi; Esteban Couto; Jorge Mendoza; Carolina Melchior do Prado; Jorge Pablo Castillo; et al. (Emerging Infectious Diseases)
We describe a large urban outbreak of feline sporotrichosis caused by Sporothrix brasiliensis fungi in Argentina. Over a 7-month period in Puerto Iguazú, which borders Brazil, we identified culture-proven sporotrichosis in 9 cases across 7 households. Public health officials should coordinate cross-border One Health actions and institute context-specific interventions.